Hubungan Kemampuan Menghafal Al Qur’an dan Motivasi Belajar Dengan Hasil Belajar PAI Siswa Madrasah Aliyah Al Fathimiyah Banjarwati Paciran Lamongan - Heru Siswanto (rogram Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2018)
This paper wants to find out 1) Is there a relationship between the ability to memorize the Koran and the learning outcomes of students of the 2017-2018 Academic Year Al-Fathimiyah Banjarwati Paciran Banjarwati Paciran. 2) Is there a relationship between learning motivation and student learning outcomes of the Aliyah Al-Fathimiyah Banjarwati Paciran Lamongan Madrasah 2017-2018 Academic Year.3) Is there a joint relationship between the ability to memorize the Koran and learning motivation with student learning outcomes Al-Fathimiyah Islamic Primary School Banjarwati Paciran Lamongan 2017-2018 Academic Year. Learning motivation is the overall driving force or drive in the student that causes learning activities and that gives direction to learning activities, so that the goals desired by students can be achieved. The type of research used in this study is a quantitative method with a correlational approach that is research designed to determine the level of relationship of different variables in one population. 3. Based on the research, that there is a jointly significant relationship between the ability to memorize the Koran and learning motivation with the learning outcomes of students of the 2017-2018 Academic Year of Al-Fathimiyah Banjarwati Paciran Banjarwati Paciran. This is shown in the results of multiple correlation analysis for the significance test obtained by the calculated F value of 24,042, then compared with the F table obtained (df) = numerical numerator (2) + df denominator (49) = 51.